Urokinase‐type plasminogen activator receptor (uPAR) as a promising new imaging target: potential clinical applications. (3rd April 2013) - Persson, Morten; Kjaer, Andreas
Summary: Urokinase‐type plasminogen activator receptor (uPAR) has been shown to be of special importance during cancer invasion and metastasis. However, currently, tissue samples are needed for measurement of uPAR expression limiting the potential as a clinical routine. Therefore, non‐invasive methods are needed. In line with this, uPAR has recently been identified as a very promising imaging target candidate. uPAR consists of three domains attached to the cell membrane via a glycosylphosphatidylinositol (GPI) anchor and binds it natural ligand uPA with high affinity to localize plasminogen activation at the cell surface. Due to the importance of uPAR in cancer invasion and metastasis, a number of high‐affinity ligands have been identified during the last decades. These ligands have recently been used as starting point for the development of a number of ligands for imaging of uPAR using various imaging modalities such as optical imaging, magnetic resonance imaging, single photon emission computer tomography (SPECT) and positron emission topography (PET). In this review, we will discuss recent advances in the development of uPAR‐targeted imaging ligands according to imaging modality. In addition, we will discuss the potential future clinical application for uPAR imaging as a new imaging biomarker.